1994
DOI: 10.1002/j.1460-2075.1994.tb06860.x
|View full text |Cite
|
Sign up to set email alerts
|

Rab escort protein-1 is a multifunctional protein that accompanies newly prenylated rab proteins to their target membranes.

Abstract: Rab proteins comprise a family of small GTPases that serve a regulatory role in vesicular membrane traffic. Geranylgeranylation of these proteins on C‐terminal cysteine motifs is crucial for their membrane association and function. This post‐translational modification is catalysed by rab geranylgeranyl transferase (Rab‐GGTase), a multisubunit enzyme consisting of a catalytic heterodimer and an accessory component, named rab escort protein (REP)‐1. Previous in vitro studies have suggested that REP‐1 presents ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
182
2
1

Year Published

1995
1995
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(193 citation statements)
references
References 46 publications
8
182
2
1
Order By: Relevance
“…GGTase I can transfer the geranylgeranylated protein directly to RhoGDI. Such a model is supported by the homology between RhoGDI and the Rab escort protein that serves such a function for geranylgeranyltransferase type II (Andres et al, 1993;Alexandrov et al, 1994). However, for Rho proteins that do not bind RhoGDI, such as RhoB, GGTase I as a cytosolic chaperone remains an attractive hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…GGTase I can transfer the geranylgeranylated protein directly to RhoGDI. Such a model is supported by the homology between RhoGDI and the Rab escort protein that serves such a function for geranylgeranyltransferase type II (Andres et al, 1993;Alexandrov et al, 1994). However, for Rho proteins that do not bind RhoGDI, such as RhoB, GGTase I as a cytosolic chaperone remains an attractive hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Alexandrow et al reported that REP-1 is associated with the GDPbound form of the rab proteins [33]. After accompanying the rab-GDP complex to the target membrane the REP-protein is released and the GDP is exchanged to GTP.…”
Section: Discussionmentioning
confidence: 99%
“…Original studies suggested that the prenylation reaction catalyzed by farnesyl transferase or GGTase I proceeds via a random sequential mechanism by which the enzyme can bind the protein and lipid substrates independently [8,9]. However, recent studies with human and yeast farnesyl transferase supported an ordered addition of substrates [10,11].In contrast with other known prenyl transferases, RabGGTase does not recognize its substrate directly but exerts its function in concert with another protein termed REP (Rab escort protein) [12,13]. Two known mammalian proteins, Eur.…”
mentioning
confidence: 99%
“…In contrast with other known prenyl transferases, RabGGTase does not recognize its substrate directly but exerts its function in concert with another protein termed REP (Rab escort protein) [12,13]. Two known mammalian proteins, REP-1 and REP-2, share 75% amino acid sequence identity and functionally overlap [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation